Role of Fasciola hepatica Small RNAs in the Interaction With the Mammalian Host - Fontenla, Santiago; Langleib, Mauricio; de la Torre-Escudero, Eduardo; Domínguez, Maria Fernanda; Robinson, Mark W.; Tort, José (Frontiers in Cellular and Infection Microbiology, 2022)
MicroRNAs (miRNAs) are important post-transcriptional regulators of gene expression being involved in many different biological processes and play a key role in developmental timing. Additionally, recent studies have shown that miRNAs released from parasites are capable of regulating the expression of host genes. In the present work, we studied the expression patterns of ncRNAs of various intra-mammalian life-cycle stages of the liver fluke, Fasciola hepatica, as well as those packaged into extracellular vesicles and shed by the adult fluke. The miRNA expression profile of the intra-mammalian stages shows important variations, despite a set of predominant miRNAs that are highly expressed across all stages. No substantial variations in miRNA expression between dormant and activated metacercariae were detected, suggesting that they might not be central players in regulating fluke gene expression during this crucial step in the invasion of the definitive host. We generated a curated pipeline for the prediction of putative target genes that reports only sites conserved between three different prediction approaches. This pipeline was tested against an iso-seq curated database of the 3' UTR regions of F. hepatica genes to detect miRNA regulation networks within liver fluke. Several functions related to the host immune response or modulation were enriched among the targets of the most highly expressed parasite miRNAs, stressing that they might be key players during the establishment and maintenance of infection. Additionally, we detected fragments derived from the processing of tRNAs, in all developmental stages analyzed, and documented the presence of novel long tRNA fragments enriched in vesicles. We confirmed the presence of at least 5 putative vtRNAs, that are expressed across different stages and enriched in vesicles. The presence of tRNA fragments and vtRNAs in vesicles raise the possibility that they could be involved in the host-parasite interaction.